2008
DOI: 10.3892/mmr_00000027
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumour cells in breast cancer: Prognostic indicators, metastatic intermediates, or irrelevant bystanders? (Review)

Abstract: Abstract. Circulating tumour cells (CTCs) have been of considerable interest for many years. The rarity of these cells presents the main challenge associated with their analysis. Current detection methods use antibody and nucleic acid techniques and are sensitive for CTC detection but limited in their utility by the occurrence of false-positive results. Despite this, there are a number of clinical studies which show that the presence of CTCs is an important prognostic indicator, particularly in the metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Circulating tumor cell (CTC) detection requires highly sensitive techniques . Baseline CTC number and treatment‐induced alterations are associated with progression free (PFS) and OS in metastatic disease . In early‐stage breast cancer, CTCs are associated with lymph node involvement and DFS …”
Section: Emerging Single Biomarkersmentioning
confidence: 99%
“…Circulating tumor cell (CTC) detection requires highly sensitive techniques . Baseline CTC number and treatment‐induced alterations are associated with progression free (PFS) and OS in metastatic disease . In early‐stage breast cancer, CTCs are associated with lymph node involvement and DFS …”
Section: Emerging Single Biomarkersmentioning
confidence: 99%
“…The counts for all controls (healthy subjects and patients with other lung diseases) were under the designated limit. In such cases, detection of CTCs is most likely a false positive result due to the extremely large numbers of blood cells in the samples [21,22]. On the other hand, Illie et al found that CTC-positive patients with tobacco-induced chronic obstructive pulmonary disease may have developed lung cancer [23].…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that not every CTC will result in a new metastatic lesion. The pool of CTCs is composed of live and actively metastasizing cells and bystanders that are passively shed into the circulation [5], [13][15], in combination with apoptotic tumor cell debris [16][18]. Alternative CTC detection strategies are needed, to isolate the metastasizing fraction, which is most likely to be found in the live CTC pool.…”
Section: Introductionmentioning
confidence: 99%